Boundary Spanning, Team Collaboration, and Branch Performance: The Mediating Role of Resource Orchestration - Insani Widya Astuti; Yasmine Nasution (Global Research Collaboration, 2026)
Increasing competition in the banking industry and the growing complexity of the business environment require branch offices to not only carry out operational functions, but also to manage resources adaptively and strategically. This study examines the influence of Boundary Spanning Activity (BSA) and Team Collaboration (TC) on Branch Performance (BP) with Resource Orchestration (RO) as an intervening variable in branches, one of state-owned bank in Indonesia. Grounded in dynamic capability and resource orchestration theory, the study adopts an explanatory quantitative approach with 110 definitive Branch Managers as the unit of observation, drawn from a population of 197 full-service branch offices (a response rate of approximately 55.8%). Data were collected through a six-point Likert scale questionnaire and analyzed using PLS-SEM with the disjoint two-stage approach via SmartPLS. Results indicate that BSA has a positive and significant effect on RO (β = 0.296; p = 0.020), and TC has a positive and significant effect on RO (β = 0.468; p = 0.001). TC also exerts a positive and significant direct effect on BP (β = 0.462; p < 0.001), and RO exerts a positive and significant effect on BP (β = 0.425; p < 0.001). Mediation analysis shows that RO partially (complementarily) mediates the effect of TC on BP, whereas RO fully mediates the effect of BSA on BP, since no direct path from BSA to BP is specified in the model. The structural model explains 65.7% of the variance in Branch Performance and 49.7% of the variance in Resource Orchestration. This study enriches the dynamic capability literature at the operational unit level of banking while offering practical implications for branch managers in optimizing resource orchestration and team collaboration to enhance branch performance.